2017
DOI: 10.1186/s12885-017-3408-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the sentinel node concept for detection of lateral pelvic lymph node metastasis in lower rectal cancer

Abstract: BackgroundThere are two lymphatic flows in lower rectal cancer; one along the inferior mesenteric artery and another towards the internal iliac artery. The benefit of dissection of lateral pelvic (LP) lymph nodes (LPLN) remains controversial. This study aimed to clarify the possibility of detecting the sentinel node (SN) of the LP region (LPSN) and examine metastasis, including micrometastasis, using a radio isotope (RI) method.MethodsIn total, 62 patients with clinical (c)T1-T4 rectal cancer were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…Moreover, studies on the lymphatic flow of the lateral ligament were mainly based on the macroscopic anatomy and on speculations from the clinical metastatic features (1,31). Yanagita et al suggested the existence of lymph node metastatic pathways between the pararectal and lateral regions, using the isotope method (37). However, this study did not indicate whether the pathway involved the lateral ligament or whether it involved the lateral ligament and other pathways.…”
Section: Fascial Structures and Lymphatic Distributionsmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, studies on the lymphatic flow of the lateral ligament were mainly based on the macroscopic anatomy and on speculations from the clinical metastatic features (1,31). Yanagita et al suggested the existence of lymph node metastatic pathways between the pararectal and lateral regions, using the isotope method (37). However, this study did not indicate whether the pathway involved the lateral ligament or whether it involved the lateral ligament and other pathways.…”
Section: Fascial Structures and Lymphatic Distributionsmentioning
confidence: 80%
“…These routes were the lateral and mesorectal drainage routes (49). Recently, Yanagita et al reported the utility of the radioisotope method by the submucosal injection of 99mTc to detect metastatic LPLNs in low rectal cancer cases (37). Thus, radioisotope methods have been used to examine lateral lymphatic drainage from the lower rectum.…”
Section: Functional Analyses Of Lymphatic Flowmentioning
confidence: 99%
“…11,13,14 However, laparoscopic LPLND is one of the most complicated surgical procedures from the viewpoint of anatomical complexity of the lateral region in the pelvis and autonomic nerve preservation. [15][16][17] Thus far, details on the lymphatic flow in the lateral region of the pelvis have not been completely clear and the quality of LPLND has been a problem for colorectal surgeons. As a result, the recurrence of lateral lesions of the pelvis after LPLND has been experienced.…”
Section: Principales Resultados Medidasmentioning
confidence: 99%
“…Recently, this concept has been applied to gastrointestinal cancer 26 . Yanagita et al 27 reported that after preoperative local radioisotope injection in 62 patients with rectal cancer, the SLN could be identified in the LatLN in 12 patients. Noura et al 28 reported that preoperative local indocyanine green dye injection in 25 patients with lower rectal cancer resulted in the identification of the SLN in 23 patients.…”
Section: Discussionmentioning
confidence: 99%